Black Feminist Bioethics: Centering Community to Ask Better Questions - James, Jennifer Elyse (The Hastings Center report, 2022)
This commentary builds off the article "Is Trust Enough? Anti-Black Racism and the Perception of Black Vaccine ‘Hesitancy,’" by Yolonda Wilson, and her assertion that the question, "Why don't Black people trust … ?" is insufficient. The commentary describes ways in which a Black feminist approach to knowledge production can facilitate centering community and can lead researchers, health care providers, and bioethicists to ask better questions. Instead of demanding that Black patients change to fit within biomedicine, people in these fields must radically reimagine biomedicine to better meet the needs of Black patients. For this to become a reality, bioethicists must work toward eliminating racism, and the field of bioethics should embrace Black feminist bioethics to work toward this goal.